Judgment of musical emotions after cochlear implantation in adults with progressive deafness - Ambert-Dahan, Emmanuèle; Giraud, Anne-Lise; Sterkers, Olivier; Samson, Séverine (Frontiers in Psychology, 2015)
While cochlear implantation is rather successful in restoring speech comprehension in quiet environments (Nimmons et al., 2008), other auditory tasks, such as music perception, can remain challenging for implant users. Here, we tested how patients who had received a cochlear implant (CI) after post-lingual progressive deafness perceive emotions in music. Thirteen adult CI recipients with good verbal comprehension (dissyllabic words ≥ 70%) and 13 normal hearing participants matched for age, gender, and education listened to 40 short musical excerpts that selectively expressed fear, happiness, sadness, and peacefulness (Vieillard et al., 2008). The participants were asked to rate (on a 0 to 100 scale) how much the musical stimuli expressed these four cardinal emotions, and to judge their emotional valence (unpleasant-pleasant) and arousal (relaxing-stimulating). Although CI users performed above chance level, their emotional judgments (mean correctness scores) were generally impaired for happy, scary, and sad, but not for peaceful excerpts. CI users also demonstrated deficits in perceiving arousal of musical excerpts, whereas rating of valence remained unaffected. The current findings indicate that judgments of emotional categories and dimensions of musical excerpts are not uniformly impaired after cochlear implantation. These results are discussed in relation to the relatively spared abilities of CI users in perceiving temporal (rhythm and metric) as compared to spectral (pitch and timbre) musical dimensions, which might benefit the processing of musical emotions (Cooper et al., 2008).